C Quick Syntax Reference - Olsson, Mikael (Springer, 2015)
The C Quick Syntax Reference is a condensed code and syntax reference to the popular C programming language, which has enjoyed some resurgence of late. C's efficiency makes it a popular choice in a wide variety of applications and operating systems with special applicability to, for instance, wearables, game programming, system level programming, embedded device/firmware programming and in Arduino and related electronics hobbies. This book presents the essential C syntax in a well-organized format that can be used as a quick and handy reference.